2016
DOI: 10.1134/s001050821603014x
|View full text |Cite
|
Sign up to set email alerts
|

Combustion heat of the Al/B powder and its application in metallized explosives in underwater explosions

Abstract: An underwater explosion test is used to determine the detonation properties of metallized explosives containing aluminum and boron powders. An oxygen bomb calorimeter (PARR 6200 calorimeter, Parr Instrument Company, USA) is used to obtain the heat of combustion of the metal mixtures. As the content of boron powders is increased, the heat of combustion of the metal mixtures increases, and the combustion efficiency of boron decreases. The highest value of the combustion heat is 38.2181 MJ/kg, with the boron cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Song et al [20][21][22] prepared the AlÀB alloy powder by a mechanical milling method and found that the combustion performance and the burning rate pressure index of the boron powder can be effectively improved. Xu et al [23] mechanically blended a certain amount of elemental B powder and Al powder, and measured the combustion enthalpy of this Al/B mixed powder by oxygen bomb calorimeter. They indicated when the content of B was 40 %, the combustion enthalpy reached the [ A large number of researches have shown that the preparation of AlÀB alloy powder can not only effectively increase the total calorific value but also optimize the oxidation and combustion performance [24].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [20][21][22] prepared the AlÀB alloy powder by a mechanical milling method and found that the combustion performance and the burning rate pressure index of the boron powder can be effectively improved. Xu et al [23] mechanically blended a certain amount of elemental B powder and Al powder, and measured the combustion enthalpy of this Al/B mixed powder by oxygen bomb calorimeter. They indicated when the content of B was 40 %, the combustion enthalpy reached the [ A large number of researches have shown that the preparation of AlÀB alloy powder can not only effectively increase the total calorific value but also optimize the oxidation and combustion performance [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of boron powder is complicated by the formation of an inert oxide layer on the particles surface, which leads to an increase in the ignition delay time and complete combustion time. To reduce the time and the temperature of boron ignition and to increase its combustion completeness, additives based on Mg, Al, Fe, Cu, Bi, Ce [10][11][12][13][14] are used, which make it possible to reduce the ignition times by up to two times [10], and the ignition temperature by 10 % [11]. In addition, the introduction of such additives makes it possible to increase the completeness of conversion [10,11,13], which makes the use of bimetal powder in HEM one of the most promising areas of research.…”
Section: Introductionmentioning
confidence: 99%
“…6 Research has shown that compared with aluminum-containing compositions, such as Al/octogen (HMX) and hexogen (RDX)/Al/ammonium perchlorate (AP), boron-containing ones, B/HMX and RDX/Al/B/AP, have a higher energy. 7 This indicates that boron is a potential candidate for use as a fuel additive in almost all energetic materials. Nevertheless, the elemental boron particles have a tight coating layer in the form of oxides and hydrates, which reduces the performance as a fuel and leads to inefficient burning.…”
Section: Introductionmentioning
confidence: 99%